Penggunaan Ejaan dalam Surat Dinas di Polres Bulukumba: Spelling in Letter Official Service in Police Resort of Bulukumba - Andi Indah Yulianti; Hasina Fajrin R; Amriani H (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2020)
Mistakes that appear in the official letter proved that until now there are many institutions, private and government, that uses the letter as a means of communication, but in the writing process still there is a mistake. The writing of official letters should be written in official or formal languages in accordance with official language letters of language. This study could reveal the misuse of spelling and the factors that caused this mistakes. The method used in this research is qualitative descriptive method using interview technique and collect examples of official service letter at Polres Bulukumba. The findings in this study are, the inaccuracy of capitalization, the use of punctuation, and the error of dictions. While the cause of the error is caused by several factors namely, (1) the language user factor which includes (a) lack of understanding of Indonesian rules, and (b) unintentional use of language; (2) environmental factors; (3) language factors that include (a) language difficulties, and (b) the influence of regional languages.